Evaluation of n-type ternary metal oxide NiMn2O4 nanomaterial for humidity sensing - Gawli, Yogesh; Badadhe, Satish S.; Basu, Aniruddha; Guin, Debanjan; Shelke, Manjusha V.; Ogale, Satishchandra (Sensors and Actuators B-Chemical, 2014)
Synthesis of mono-dispersed oleic acid (OA) capped NiMn2O4 (NMO) nanoparticles and their use for humidity sensing is reported. Oleic acid capped NMO (NMO-cOA) nanoparticles are synthesized from nickel oleate and manganese oleate complex. NiMn2O4 is obtained by removing oleic acid capping at 500 degrees C in air. X-ray diffraction analysis shows formation of pure NiMn2O4 phase which is also confirmed by HRTEM-SAED analysis. The TEM analysis also shows that the nanoparticles are nearly mono-dispersed. Doctor bladed films of NMO nanoparticles are seen to exhibit excellent humidity sensing property. The resistivity is seen to change by two orders with humidity change from 11% RH to 92% RH with fairly good linearity over the entire range. The response and recovery times are also fast. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Humidity; Impedance; Nanoparticles; NiMn2O4; Oleic acid; Sensor

High performance all-organic flexural piezo-FET and nanogenerator via nanoscale soft-interface strain modulation - Dhakras, Dipti; Gawli, Yogesh; Chhatre, Shraddha; Wadgaonkar, Prakash; Ogale, Satishchandra (Physical Chemistry Chemical Physics, 2014)
Flexural strain fields are encountered in a wide variety of situations and invite novel device designs for their effective use in sensing, actuating, as well as energy harvesting (nanogenerator) applications. In this work we demonstrate an interesting all-organic device design comprising an electrospun P(VDF-TrFE) fiber-mat built directly on a conducting PANI film, which is also grown on a flexible PET substrate, for flexural piezo-FET and nanogenerator applications. Orders of magnitude stronger modulation of electrical transport in PANI film is realized in this device as compared to the case of a similar device but with a uniform spin-coated P(VDF-TrFE) film. We find that in the flexural mode of operation, the interaction between the laterally modulated nanoscale strain field distributions created by the fibers and the applied coherent strain field strongly influences the carrier transport in PANI. The transport modulation is suggested to occur due to strain-induced conformational changes in P(VDF-TrFE) leading to changes in carrier localization-delocalization. We further show that the fiber-mat based device system also works as an efficient nanogenerator capable of delivering power for low power applications.

3D Polyaniline architecture by concurrent inorganic and organic acid doping for superior and robust high rate supercapacitor performance - Gawli, Yogesh; Banerjee, Abhik; Dhakras, Dipti; Deo, Meenal S.; Bulani, Dinesh; Wadgaonkar, Prakash P.; Shelke, Manjusha; Ogale, Satishchandra (Scientific Reports, 2016)

Robust highly flexible all-solid-state micro pseudocapacitor based on ternary oxide CuCo2O4 having ultrathin porous nanowall type morphology blended with CNT - Basu, Aniruddha; Bhardwaj, Monika; Gawli, Yogesh; Rode, Chandrasekhar V.; Ogale, Satishchandra B. (Chemistryselect, 2016)
In this work we demonstrate a facile approach to the fabrication of all solid state flexible interdigitated micro pseudocapacitor device using pre-synthesized CuCo2O4 (CCO) ternary metal oxide as the electrode material. The hydrothermally synthesized CCO exhibits a peculiar 3D interconnected aligned porous nanowall type morphology which is highly desirable for storage as well as charge transfer. The device is fabricated using CO2 laser scribing technique and the PVA-H3PO4 gel electrolyte is used as the electrolyte. The as-synthesized CCO as well as its blend with 10 wt.% CNT are examined for the electrochemical performance. CNT blending is shown to reduce the charge transfer resistance dramatically, thereby enhancing the pseudo capacitance. The areal capacitance of 2.29 mF cm(-2) is obtained from the solid state device. Moreover, the CCO-CNT electrode also shows a high stability upto 9000 cycles without a sign of further decay. Importantly, the devices also retain over 65% of their initial capacitance after 1000 large angle (608) bending cycles and 93% of the initial capacitance under 1208 bending condition, thanks to the mechanical flexibility afforded by CNTs without disrupting conducting paths.

G - C3N4 (2D)/CdS (1D)/rGO (2D) dual-interface nano-composite for excellent and stable visible light photocatalytic hydrogen generation - Tonda, Surendar (International Journal of Hydrogen Energy, 2017)
A 2D/1D/2D dual-interface nano-composite configuration in the form of CdS nanorods sandwiched between g-C3N4 and rGO sheets with intimate interfacial contact is synthesized by a facile wet-chemical method and is shown to exhibit excellent photocatalytic H2 generation under visible-light irradiation. In particular, the optimal g-C3N4/CdS/rGO dual-interface nano-composite shows H2 production rate of ∼4800 μmol h-1 g-1, which is almost 44, 11 and 2.5 times higher than that shown by pure g-C3N4 nanosheets, and the g-C3N4/rGO and g-C3N4/CdS single interface heterostructures, respectively. It is shown that the synergic effects involving the band structure match and close interfacial contact, which can accelerate the separation and transfer of photoinduced charge carriers, and the enhanced visible-light absorption together contribute to the impressive photocatalytic performance and photostability of the g-C3N4/CdS/rGO ternary nano-composite system. Specific advantages of a dual-interface triple-composite system over a single interface case(s) are also brought out.
Keywords: charge transfer; Dual Interface; G - CN; H Generation; Hetero Structure; Nano - Composite

Hexaphosphate-derived phosphorus-functionalized carbon for lithium-ion battery anode - Gawli, Yogesh; Wahid, Malik; Fernandez, Rohan; Kothari, Dushyant; Shelke, Manjusha; Ogale, Satishchandra B. (Chemistryselect, 2017)
We show that high-temperature annealing of a dried hexaphosphate, namely phytic acid, renders activated (micro-porous) and phosphorus-functionalized graphene like carbon in a one-step process. At high enough temperature few volatile phosphates serve as porogen-forming entities while other groups reactively functionalize the carbon surface. The optimized material has high effective surface area due to the presence of defect states. As an anode material for Li-ion battery, it exhibits a reversible capacity that is double that of the graphite and is stable for 1000 cycles even at a high current of 5 A g(-1). This result is attributed to the concurrent presence of micropores and phosphorus containing groups in the carbon matrix.

Low-dimensional hybrid perovskites as high performance anodes for alkali-ion batteries - Tathavadekar, Mukta; Krishnamurthy, Shrreya; Banerjee, Aparna; Nagane, Satyawan; Gawli, Yogesh; Suryawanshi, Anil; Bhat, Suresh; Puthusseri, Dhanya; Mohite, Aditya D.; Ogale, Satishchandra (Journal of Materials Chemistry A, 2017)
State-of-the-art Li (or Na) ion batteries work by insertion/extraction of the alkali metal ions into a porous electrode material, where the overall capacity is strongly dependent on the accessibility of the host material interior to the ions. On the other hand, the performance stability depends on various factors governed by the specific constitution of the electrode. Here we show that molecularly engineered low-dimensional hybrid perovskites can work as excellent anode materials for alkali-ion batteries. We measure a high reversible capacity of 646 mA h g(-1) at 100 mA g(-1) with good stability tested up to 250 cycles for the benzidine mediated lead iodide based 1D system. An ex situ analysis of the electrodes reveals that the storage primarily occurs via the Li-x(or Na-x)Pb alloying/de-alloying process. We anticipate that these results open a new direction for the use of low-dimensional hybrid perovskites for energy storage applications.
Keywords: Generation; Inorganic-Organic Hybrid; Lead Iodide; lithiation-intramolecular electrophilic reaction; Na-Air Battery; Negative Electrodes; Organometal Halide perovskites; PB; Sequential Deposition; Solar-cells

Nanotubular hard carbon derived from renewable natural seed gel for high performance sodium-ion battery anode - Sharma, Neha; Gawli, Yogesh; Ahmad, Absar; Muhammed, Musthafa; Ogale, Satishchandra (Chemistryselect, 2017)
Electrical energy storage devices such as batteries and supercapacitors are perhaps the most researched topic today in view of its critical implications for the successful implementations of various renewable energy harvesting initiatives. Amongst the various battery systems being currently examined, the Li-battery continues to be a main player, but the Na-ion battery has been attracting significant attention lately due to the concerns about the limited reserves and high cost of Li. Hard carbon is recognized to be a good anode material for Na-battery. In this work we present a novel approach to synthesize such hard carbon from a natural gel derived from the commonly used Basil seeds (Osimum Basilicum) which swell 30 times their weight by absorbing water. The hard carbon obtained by pyrolysis of the freeze-dried mucilage possesses sheet-like and tubular morphology with decorated surface defects attributed to the presence of oxygen functionalities. This hard carbon shows a good reversible capacity of 195 mAh g(-1) at 0.1A g(-1) with an impressive approximate to 91% retention of initial capacity after 300 cycles and sustains high current densities with not much change in capacity value.

High and reversible lithium ion storage in self-exfoliated triazole-triformyl phloroglucinol-basedcovalent organic nanosheets - Haldar, Sattwick; Roy, Kingshuk; Nandi, Shyamapada; Chakraborty, Debanjan; Puthusseri, Dhanya; Gawli, Yogesh; Ogale, Satishchandra; Vaidhyanathan, Ramanathan (Advanced Energy Materials, 2018)
Covalent organic framework (COF) can grow into self-exfoliated nanosheets. Their graphene/graphite resembling microtexture and nanostructure suits electrochemical applications. Here, covalent organic nanosheets (CON) with nanopores lined with triazole and phloroglucinol units, neither of which binds lithium strongly, and its potential as an anode in Li-ion battery are presented. Their fibrous texture enables facile amalgamation as a coin-cell anode, which exhibits exceptionally high specific capacity of approximate to 720 mA h g(-1) (@100 mA g(-1)). Its capacity is retained even after 1000 cycles. Increasing the current density from 100 mA g(-1) to 1 A g(-1) causes the specific capacity to drop only by 20%, which is the lowest among all high-performing anodic COFs. The majority of the lithium insertion follows an ultrafast diffusion-controlled intercalation (diffusion coefficient, D-Li(+) = 5.48 x 10(-11) cm(2) s(-1)). The absence of strong Li-framework bonds in the density functional theory (DFT) optimized structure supports this reversible intercalation. The discrete monomer of the CON shows a specific capacity of only 140 mA h g(-1) @50 mA g(-1) and no sign of lithium intercalation reveals the crucial role played by the polymeric structure of the CON in this intercalation-assisted conductivity. The potentials mapped using DFT suggest a substantial electronic driving-force for the lithium intercalation. The findings underscore the potential of the designer CON as anode material for Li-ion batteries.